Diagnostic Accuracy and Outcome of Assessment Pathways for Women Recalled after Breast Cancer Screening - maluze, Ugochukwu (British Journal of Healthcare and Medical Research, 2026)
Introduction: Breast cancer is the most commonly diagnosed cancer among women globally, with an estimated 2.26 million new cases in 2020. The risk factors of breast cancer include age, genetic mutation and family history, racial and ethnic disparities, Increase in breast tissue density, etc. Early detection through organized screening programs plays a crucial role in improving survival by identifying cancer at stages when treatment is more likely to be curative. However, screening and diagnostic results can sometimes be misinterpreted, leading to false positives, false negatives, unnecessary follow-up tests, or over-diagnosis. Although digital mammography remains the standard, additional imaging methods are now used for high-risk individuals and those with dense breast tissue. Aims and Objectives: To evaluate the diagnostic accuracy, and the clinical, psychological, and diagnostic outcomes following recall after routine breast screening. The studies include a Cohort studies, Observational and Case-Control studies, Diagnostic accuracy and Screening Programs evaluations. Participants includes women aged 40 and older undergoing routing breast screening and were called back for additional assessment. Studies were conducted in several countries including Norway, Spain, etc. Ethical approval was not required for the studies as the participants clinical information was anonymized across all selected studies. Methodology: Data were collected using a computerized search strategy as the principle source of information from European Journal of Public Health, Journal of Breast Imaging, PubMed, etc. Results: Findings from the Randomized and Population-based Cohort study suggested that the screen-detected breast cancers indicated over-diagnosis rate of 14-39% with limited quality evidence. Data from the Observational studies estimated the 10-years cumulative probability of false-positive results with Film and Digital Mammography of 49% with limited quality evidence. Findings from the Cohorts studies showed that those women called back for further evaluation reported higher levels of anxiety, distress and pains with a moderate quality evidence. The harm of radiation exposure from mammography screening is based on only three modeling studies with moderate quality evidence.